2011
DOI: 10.1007/s10616-011-9377-2
|View full text |Cite
|
Sign up to set email alerts
|

Fucose content of monoclonal antibodies can be controlled by culture medium osmolality for high antibody-dependent cellular cytotoxicity

Abstract: Antibody-dependent cellular cytotoxicity (ADCC) is dependent on the fucose content of oligosaccharides bound to monoclonal antibodies (MAbs). As MAbs with a low fucose content exhibit high ADCC activity, it is important to control the defucosylation levels (deFuc%) of MAbs and to analyze the factors that affect deFuc%. In this study, we observed that the deFuc% was inversely related to culture medium osmolality for MAbs produced in the rat hybridoma cell line YB2/0, with r 2 values as high as 0.92. Moreover, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 77 publications
0
35
0
Order By: Relevance
“…genetic engineering of recombinant cell lines (Louie et al, 2016;Yamane-Ohnuki et al, 2004); (b) addition of enzyme inhibitors (Allen et al, 2016;Okeley et al, 2015); (c) modification of the levels of cofactors and substrates involved in glycosylation, including supplementation with alternative sugars (Hossler et al, 2014;Hossler et al, 2017); and (d) fine-tuning of cell culture process parameters (Konno et al, 2012). Of the many cell culture process parameters known to impact glycosylation previously (Hossler, Khattak, & Li, 2009), osmolality was shown to affect afucosylation (Konno et al, 2012).…”
mentioning
confidence: 99%
“…genetic engineering of recombinant cell lines (Louie et al, 2016;Yamane-Ohnuki et al, 2004); (b) addition of enzyme inhibitors (Allen et al, 2016;Okeley et al, 2015); (c) modification of the levels of cofactors and substrates involved in glycosylation, including supplementation with alternative sugars (Hossler et al, 2014;Hossler et al, 2017); and (d) fine-tuning of cell culture process parameters (Konno et al, 2012). Of the many cell culture process parameters known to impact glycosylation previously (Hossler, Khattak, & Li, 2009), osmolality was shown to affect afucosylation (Konno et al, 2012).…”
mentioning
confidence: 99%
“…In these biotherapeutic molecules, N-glycans are linked to the two conserved asparagine residues (Asn 297) in the CH2 domain of the Fc region 61 . A large number of reports describe various impacts of glycosylation on the quality attributes of biologics including in vivo efficacy [62][63][64] , pharmacokinetics (PK) 11 , antibody-dependent cellular cytotoxicity (ADCC) 63,65 and complementdependent cytotoxicity (CDC) activities 66 , stability and overall structure of the molecule 63 , clearance and half-life in vivo 10 as well as immunogenicity 10,67 . Non-fucosylated therapeutic antibodies exhibit 50 to 1,000-fold higher efficacy than their fucosylated counterparts 65 due, in most cases, to enhanced ADCC activity 68 .…”
Section: Glycosylationmentioning
confidence: 99%
“…A large number of reports describe various impacts of glycosylation on the quality attributes of biologics including in vivo efficacy [62][63][64] , pharmacokinetics (PK) 11 , antibody-dependent cellular cytotoxicity (ADCC) 63,65 and complementdependent cytotoxicity (CDC) activities 66 , stability and overall structure of the molecule 63 , clearance and half-life in vivo 10 as well as immunogenicity 10,67 . Non-fucosylated therapeutic antibodies exhibit 50 to 1,000-fold higher efficacy than their fucosylated counterparts 65 due, in most cases, to enhanced ADCC activity 68 . Given the abundance of research efforts in this area, it is no surprise that many have concluded that glycosylation is one of the main areas requiring development 69 to improve efficacy 70 and safety 10,70 of next generation therapeutics 61 .…”
Section: Glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycosylation is one of very important post-translational modifications because it can have significant impact on antibody-dependent cell-mediated cytotoxicity (ADCC) activity [3,4], complement-dependent cytotoxicity (CDCC) activity [5], clearance [6] and immunogenicity [7,8]. Protein glycosylation can be significantly impacted by the host cell line, clone, media composition, feeding strategy and downstream processing conditions [9][10][11]. Therefore, N-glycosylation analysis of monoclonal antibody is widely performed in the biopharmaceutical development, and in some cases is used as release assay when glycosylation is established as a critical quality attribute [12].…”
Section: Introductionmentioning
confidence: 99%